CRD IV/CRR Package and its Impact on the European Union Banking Market (Economic and Political Thought, 2013)
In April 2013, the European Parliament approved new guidelines for theadmission of banks to the activities in the European Union market, as wellas the prudential supervision of credit institutions and investment firms. Thenew provisions have been included in the so-called CRD IV/CRR package.The aim of the article is to present the new regulations of the banking marketintroduced by the CRD IV/CRR package and assess their impact on thebanking sector in the European Union.